Pengaruh Green Marketing terhadap Citra Merek dan Loyalitas Konsumen - Ibrahim, Darmawansah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the effect of green marketing on brand image and consumer loyalty in companies that implement environmentally friendly marketing strategies. Green marketing is a marketing approach that emphasizes sustainability and environmental responsibility, which can enhance consumers’ positive perceptions of the brand. This research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to consumers who have used products or services from companies practicing green marketing. The results indicate that the implementation of green marketing has a positive and significant effect on brand image. A positive brand image subsequently contributes to increased consumer loyalty, leading consumers to make repeat purchases and recommend products to others. These findings confirm that environmentally friendly marketing strategies not only benefit the environment but also enhance brand value and foster long-term relationships with consumers.